Religion and recovery from PTSD - Koenig, Harold George (Jessica Kingsley Publishers, 2019)
Post-traumatic stress disorder (PTSD) -- Evidence-based treatments for PTSD -- Healing from war in religious scriptures -- Religion and coping with severe trauma -- Prevention of PTSD and impact of trauma on religion -- Recovery from PTSD and impact on posttraumatic growth -- Moral injury and PTSD -- Identifying moral injury -- Religious/spiritual treatments for PTSD and moral injury -- Spiritually-integrated cognitive processing therapy for moral injury and PTSD -- How religion affects PTSD -- Recommendations, summary and conclusions.